Managing trust in strategic alliances - Das, T. K. 1938- (Research in strategic alliances., 2018)
Managing Trust in Strategic Alliances is a volume in the book series Research in Strategic Alliances that focuses on providing a robust and comprehensive forum for new scholarship in the field of strategic alliances. In particular, the books in the series cover new views of interdisciplinary theoretical frameworks and models, significant practical problems of alliance organization and management, and emerging areas of inquiry. The series also includes comprehensive empirical studies of selected segments of business, economic, industrial, government, and non-profit activities with wide prevalence of strategic alliances. Through the ongoing release of focused topical titles, this book series seeks to disseminate theoretical insights and practical management information that should enable interested professionals to gain a rigorous and comprehensive understanding of the field of strategic alliances.Managing Trust in Strategic Alliances contains contributions by leading scholars in the field of strategic alliance research. The 10 chapters in this volume deal with significant issues relating to the management of trust in strategic alliances. These issues include the role of trust in value creation and appropriation, the dialectics of trust, control, and risk in multilateral R&D alliances, protecting trustworthiness in open and closed alliance networks, balancing trust and distrust, trust and cost disclosure, trust and control, foreign partner's trust in international strategic alliances, a multilevel approach to trust, trust in service supply networks, and trust-building in public-private strategic alliances. The chapters contain empirical as well as conceptual treatments of the selected topics, and collectively present a wide-ranging review of the noteworthy research perspectives on managing trust in strategic alliances.